Wet sieving a complex tell: Implications for retrieval protocols and studies of animal economy in historical periods. (June 2017) - Sapir-Hen, Lidar; Sharon, Ilan; Gilboa, Ayelet; Dayan, Tamar
Abstract: The understanding that fine mesh sieving is the optimal procedure for the recovery of minute finds poses two challenges for archeologists of historical periods: it is costly and time consuming, and it puts into question the value of data collected in excavations where sieving was conducted minimally or not at all. That hand picking causes loss of data pertaining to microfaunal remains is indisputable, but the extent of information loss regarding larger fauna is not as clear. In order to evaluate these challenges for macrofaunal remains, we carried out, for the first time, a comprehensive sieving experiment at Tel Dor, a multi-layered complex site, the most prominent site type in historical periods. We examine the effects of wet sieving on the macro- and microfauna frequencies, and discuss its implications in terms of the interpretations of the faunal assemblages and the choice of excavations' collection protocols. We demonstrate that while sieving has a substantial effect on microfauna frequencies, it has a limited effect on those of the macrofauna. We also suggest that faunal assemblages of livestock animals that were hand collected or partially sieved, are valid for comparison with sieved assemblages. Finally, we call for an explicit presentation of the retrieval protocol in site reports and other studies, differentiating clearly between sieved and un-sieved material, and raise some points for future discussion. Highlights: We conducted a comprehensive sieving experiment at a multi-layered tell, the most prominent site type in historical periods. Wet sieving has a limited effect on macrofauna frequencies. Microfauna are retrieved only by careful sieving, otherwise these data are almost completely lost. Our results reinforce the importance of the presence of a zooarchaeologist in the field. An explicit presentation of the retrieval protocol in site reports and other studies should be mandatory.